Prevalence of Smoking Among 4 Licensed Types of Nursing Personnel in Japan: An Epidemiological Study. (July 2019) - Jike, Maki; Nakaita, Ikumi; Uchiyama, Makoto; Yokose, Hiromi; Kubota, Satomi; Sezai, Izumi; Muranaka, Mineko; Ohida, Takashi; Kamata, Kumiko
There is a high prevalence of smoking among nursing personnel, despite the fact that nursing is a health care profession. In Japan there are 4 types of licensed nursing professionals. However, the prevalence of smoking among different types of licensed personnel has not been clarified. We attempted to clarify the prevalence of smoking among the various types of licensed nursing personnel and the factors associated with it. Among the members of the Japanese Nursing Association, 6000 nurses were randomly selected. The participants were sent a questionnaire on smoking habits, personal characteristics, lifestyle habits, and employment status by mail. Current smokers accounted for 1.3% of public health nurses, 4.0% of midwives, 8.2% of registered nurses, and 16.3% of assistant nurses. The license type of nursing personnel was a factor significantly associated with current smoking.